Construction of Heart Beat Monitoring System - Godfrey U., Aimua; Mojisola R, Usikalu; Akinwumi, Akinpelu (International Journal of Psychosocial Rehabilitation, 2020)
The aim of this paper is to develop and construct a budget heartbeat monitoring system using Ardiuno by measuring the electrical heart information known as electrocardiography (ECG). The detector was constructed using sensor SEN-11574 and designed with analog to digital converter by converting different wavelengths of light sources. The optical sensing mechanisms of the pulse sensor detect the differences in blood round the wrist and the fingertip. The developed device measured the heartbeat in three periods. Firstly, the sensor detected the pulse in the wrist and the finger-tip, in the second phase, the signal was amplified and digitized. In the final phase the digitized signal is sent through the serial port to the Arduino where the heart rate is calculated and displayed on the LCD screen. The constructed device was used to detect heart beat rate of willing individuals. The heart beat rate obtained ranged from 60 to 102 bpm and 55 to 100 bpm for male and female respectively.